Traditional Role In The District Surabaya - Lastianti, Siwidyah Desi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This study aims to determine: (1) the district government Surabaya in determining the block in Citra Niaga Market location Surabaya; (2) the implementation of the allotment of Block G-2; (3) increase in local revenues derived from market sectors. The data used is data 2003 to 2005 from the Office of Market and Regional Financial Management Agency Surabaya. Primary data has also used that data obtained from the heads of the market and traders in Citra Niaga Market Surabaya. The results of this research are: 1) the efforts made by the government in overcoming the problems Surabaya by: (a) re-creating the kiosks/stalls in block G-2 is optimal; (b) rearranging merchants to trade freely in the street Seroja to enter into site Citra Niaga Market Block G-2; (c) issuing policies related to the market environment is clean, beautiful and comfortable; (d) issue a policy concerning Retribution in block G-2, which is equal to the Retribution rates for merchants selling goods on the street Seroja (behind the market Citra Niaga), this will affect the selling price of goods sold by traders in the block G- 2 is equal to the selling price of the merchant on the street Seroja; (e) provides that a policy of cheap money installments for traders in block G-2 that will be able to attract other merchants to hire kiosk / Los block the G-2; (2) Contributions Retribution Citra Niaga to the PAD market is still small, need to be improved.